2001
DOI: 10.1111/j.1744-7348.2001.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Races and virulence of Fusarium oxysporum f.sp. cubense on local banana cultivars in Kenya

Abstract: SummaryVirulence of 31 Kenyan isolates of Fusarium oxysporum obtained from bananas showing symptoms of Panama disease was tested against the differential banana cvs Bluggoe, Gros Michel, Dwarf Cavendish, and two other local cvs Muraru and Wang'ae. Seventeen isolates were assigned to either race 1 or race 2 of F. oxysporum f.sp. cubense (FOC). Race 4 was not apparent in this sample of 31 isolates from Kenya as none were pathogenic to cv. Cavendish, and no wilted Cavendish have been observed in field surveys in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…It expands on the works of Arinaitwe et al (2019) [ 33 ], which found seven Mchare cultivars were susceptible to Foc race 1 in screen house evaluations, and the report of Kung’U and Jeffries (2001) [ 34 ] which found a Muraru cultivar in Kenya to be affected by Fusarium wilt. Kung’U and Jeffries (2001) [ 34 ] also showed Muraru to be less susceptible to Foc race 1 (VCGs 0124 and 01220) than Bluggoe and Gros Michel bananas [ 34 ]. The resistant diploid EAHB cultivars identified in the current study, therefore, are potentially useful replacements for the susceptible cultivars in the area.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It expands on the works of Arinaitwe et al (2019) [ 33 ], which found seven Mchare cultivars were susceptible to Foc race 1 in screen house evaluations, and the report of Kung’U and Jeffries (2001) [ 34 ] which found a Muraru cultivar in Kenya to be affected by Fusarium wilt. Kung’U and Jeffries (2001) [ 34 ] also showed Muraru to be less susceptible to Foc race 1 (VCGs 0124 and 01220) than Bluggoe and Gros Michel bananas [ 34 ]. The resistant diploid EAHB cultivars identified in the current study, therefore, are potentially useful replacements for the susceptible cultivars in the area.…”
Section: Discussionsupporting
confidence: 59%
“…Until recently, a limited amount of information was available on the response of diploid EAHB bananas to Foc race 1, despite the seasonal appearance of Fusarium wilt on Mchare and Muraru bananas in Tanzania and Kenya, respectively [ 33 , 34 ]. This lack of information delayed the management of banana Fusarium wilt in areas where losses occur, including efforts to improve EAHB diploids genetically for Fusarium wilt resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triploid EAHB bananas (AAA), commonly known as Matoke bananas, are resistant to Foc Lineage VI strains (Kangire et al 2000;Tushemereirwe et al 2000). However, diploid bananas (AA) grown in some parts of Kenya (Onyango et al 2011), and known as Muraru bananas, are susceptible to Fusarium wilt (Kung'u and Jeffries 2001). The susceptibility of Mchare (AA) bananas grown in the Kilimanjaro region in Tanzania (De Langhe et al 2001) has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Race classification has been used to distinguish among Foc strains, and is based on the pathogen's ability to cause disease to a differential set of banana cultivars. There are three Foc races; race 1, race 2 and race 4, causing disease to Gros Michel, Bluggoe and Cavendish cultivars, respectively (Stover 1962;Kung'u and Jeffries 2001;Ploetz 2006Ploetz , 2015a. The identification of Foc races is, however, not always reliable as some banana varieties are predisposed to infection by Foc in unfavourable environments (Ploetz 2015a).…”
Section: Introductionmentioning
confidence: 99%